A study of impact of stress: examinations on menstrual cycle among medical students - Rathi, Anant Kumar; Agrawal, Megha; Baniya, Girish Chandra (International Journal of Research in Medical Sciences, 2019)
Background: Premenstrual Syndrome (PMS), a common problem among adolescent girls, is associated with various physical, mental and behavioral symptoms that lead to social and occupational impairment. Stress has also been hypothesized to be an important etiologic factor. Examination stress may also be responsible for affecting the premenstrual symptoms. The objectives of this study was to study the impact of exam stress on the menstrual cycle and the relationship of perceived stress with the severity of premenstrual symptoms. Methods: This was a cross-sectional observational study conducted among female medical students of final MBBS, who were candidate of upcoming exams. They were assessed on semi structured socio-demographic and menstrual history proforma, ACOG guidelines, DSM-5 criteria, Perceived Stress Scale (PSS) and Premenstrual Symptom Screening Tool (PSST). Results: As per ACOG guidelines, 66% participants had PMS and 6% participants had PMDD according to DSM-5 criteria. On PSST total 88% participants had premenstrual symptoms and out of them 58% had mild/no PMS while 30% had moderate to severe PMS. 5% participants also fulfilled criteria for PMDD on PSST. Stress was found to be mild in 26% and moderate in 74% participants on PSS. PMS was found in 93.75% participants who had painful menstruation (dysmenorrhea) and this association was statistically significant. Data wise 73.1% participants having mild stress had PMS, while 93.2% participants having moderate stress, had PMS and this association was found to be statistically significant. Surprisingly not a single participant consulted to any health care provider for their menstruation related problems. Conclusions: Premenstrual Syndrome is common in adolescent girls and exam stress is an important etiological factor. PMS/PMDD was found significantly higher in participants who had dysmenorrhea and moderate stress. A positive and highly significant correlation was also found between the severity of stress and severity of premenstrual symptoms.